2017
DOI: 10.1097/ico.0000000000001390
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Keratitis in Toronto: A 16-Year Review of the Microorganisms Isolated and the Resistance Patterns Observed

Abstract: There has been a decreasing trend in the number of isolates in gram-positive microorganisms over the past 16 years. An increasing trend in resistance for various antibiotics against gram-negative and gram-positive isolates was identified. High susceptibility to vancomycin reinforced the empirical use of fortified tobramycin and vancomycin in the initial management of severe bacterial keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 46 publications
6
46
0
Order By: Relevance
“…The proportion of gram-negative bacteria among total bacterial keratitis has been increasing recently. Tam et al reported that the proportion of gram-negative bacterial keratitis increased from 19% in 2000–2003 to 30% in 2012–2015 [ 12 ]. Pseudomonas species has continued to be the most common isolate of gram-negative bacterial keratitis; the proportion varies among countries, ranging from 10% of cases in North America [ 12 14 ], 24.4% in Taiwan [ 15 ], 32.5% in South Korea [ 16 ], and up to 52% in South India [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of gram-negative bacteria among total bacterial keratitis has been increasing recently. Tam et al reported that the proportion of gram-negative bacterial keratitis increased from 19% in 2000–2003 to 30% in 2012–2015 [ 12 ]. Pseudomonas species has continued to be the most common isolate of gram-negative bacterial keratitis; the proportion varies among countries, ranging from 10% of cases in North America [ 12 14 ], 24.4% in Taiwan [ 15 ], 32.5% in South Korea [ 16 ], and up to 52% in South India [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous use of antimicrobial antibodies has been proven effective for some infections such as Bezlotoxumab [35] in the treatment of Clostridium difficile toxin B and palivizumab [36] for respiratory syncytial virus and, as previously mentioned, MEDI3902 has been shown effective in Pseudomonas keratitis prophylaxis [3]. Since they are unconventional antimicrobials, microbes resistant to conventional antibiotics are less likely to have pre-existing resistance mechanisms to mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations can be done to determine its efficacy when given in combination with various broad-spectrum antibiotics which has been [41]. For example, tobramycin is often the standard for P. aeruginosa infections tobramycin's efficacy in the treatment of keratitis is limited [42], a previous study investigated the efficacy of tobramycin and MEDI3902 in combination [3]. Further investigation of possible combination treatments is worthy of consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, S. aureus and P. aeruginosa have been identified by the World Health Organization as 'High' and 'Critical' priority targets, in the development of new antibiotics [38]. Evidence of increasing antibiotic resistance among ocular isolates is provided by longitudinal studies [39,40] and of particular concern is the observation that resistance to fluoroquinolones is increasing for both Methicillin Susceptible (MSSA) and Methicillin Resistant (MRSA) S. aureus strains [40]. In the UK, fluoroquinolones are currently used as the first-line antibiotic in the treatment of bacterial keratitis [41].…”
Section: Antibiotic Resistance In Biofilmsmentioning
confidence: 99%